Multidimensional poverty in Bhutan : estimates and policy implications - Santos, M; Ura, K (Oxford Poverty & Human Development Initiative (OPHI), 2008)
This paper estimates multidimensional poverty in Bhutan applying the methodology developed by Alkire and Foster using the 2007 Bhutan Living Standard Survey data. Five dimensions are considered for estimations in both rural and urban areas: income, education, room availability, access to electricity and access to drinking water, and two additional dimensions are considered for estimates in rural areas only: access to roads and land ownership. It is found that multidimensional poverty is mainly a rural phenomenon, although urban areas present non-depreciable levels of deprivation in room availability and education. Within rural areas, weighting each indicator equally, deprivation in electricity, education room and income are the highest and similar in contribution to aggregate multidimensional poverty. When weights derived from the Gross National Happiness Survey are used, income deprivation significantly increases its contribution as it receives a higher weight. Rankings of districts by their poverty estimate are found to be robust for a wide range of poverty cutoffs. The methodology is suggested as a potential formula for national poverty measurement as well as a tool for budget allocation.